Analysis of Microarrays by MALDI‐TOF MS1. Issue 29 (11th June 2013) - Beloqui, Ana; Calvo, Javier; Serna, Sonia; Yan, Shi; Wilson, Iain B. H.; Martin‐Lomas, Manuel; Reichardt, Niels Christian
<x xml:space="preserve">Abstract</x> Ligand libraries can be printed onto a sandwich composed of activated lipids embedded in a hydrophobic layer conjugated to an indium–tin oxide (ITO) surface. Arrays produced this way can be analyzed by fluorescence spectroscopy and mass spectrometry. Applications include the assignment of enzyme specificity, the profiling of glycoforms and the identification of lectins.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>